IL-21 Modulates Release of Proinflammatory Cytokines in LPS-Stimulated Macrophages through Distinct Signaling Pathways - Su-nan Li; Wei Wang; Shou-peng Fu; Jian-fa Wang; Hong-mei Liu; Shan-shan Xie; Bing-run Liu; Yang Li; Qing-kang Lv; Zhi-qiang Li; Wen-jing Xue; Bing-xu Huang; et al. (Hindawi Limited, 2013)
The aim of this study was to investigate the anti-inflammatory effect of IL-21 on LPS-induced mouse peritoneal macrophages. The results showed that IL-21 significantly inhibited LPS-induced mRNA expression of IL-1β, TNF-α, and IL-6 in macrophages, but not of IFN-γ, IL-10, CCL5, or CXCL2. ELISA analysis showed that IL-21 also suppressed LPS-induced production of TNF-α and IL-6 in culture supernatants. Western blot analysis showed that IL-21 clearly inhibited ERK and IκBα phosphorylation and NF-κB translocation in LPS-stimulated macrophages, but it increased STAT3 phosphorylation. Flow cytometric and Western blot analysis showed that IL-21 decreased M1 macrophages surface markers expression of CD86, iNOS, and TLR4 in LPS-stimulated cells. All results suggested that IL-21 decreases IL-6 and TNF-α production via inhibiting the phosphorylation of ERK and translocation of NF-κB and promotes a shift from the M1 to M2 macrophage phenotype by decreasing the expression of CD86, iNOS, and TLR4 and by increasing STAT3 phosphorylation in LPS-stimulated cells.